2210. An Online Survey of Hepatitis C Testing Attitudes and Practice Habits Among Residents at an Urban Medical Center. (26th November 2018) - Zucker, Jason; Carnevale, Caroline; Scherer, Matthew; Cohall, Alwyn; Sobieszczyk, Magdalena; Gordon, Peter; Olender, Susan
Abstract: Background: The hepatitis C virus (HCV) is the most common blood-borne infection; treatments are well tolerated, highly effective, and improve health outcomes. A recent blinded seroprevalence study of ED patients identified an undiagnosed HCV prevalence 0.8%. New York State recently highlighted a strategic plan to reduce the incidence and prevalence of HCV through aggressive testing, linkage, and treatment. To evaluate HCV screening practices, we conducted a survey of resident attitudes and practice habits surrounding HCV screening. Methods: From August 1, 2017 to April 30, 2018 we conducted an anonymous online survey to examine attitudes about sexual health screening among residents at an upper Manhattan academic medical center. Response rates were 22% (33) for internal medicine (IM), 45% (35) for pediatrics (Peds), and 21% (10) for emergency medicine (EM). Results: A majority of IM residents (61%) agreed that HCV screening was one of their responsibilities as compared with Peds (23%, P = 0.002) and EM residents (20%). This differed from HIV testing where the majority of residents across disciplines (73, 71, 60%) considered HIV screening to be their responsibility. IM residents were more likely to agree that it is important to screen for HCV in all care settings. However, less than half of them considered HCV screening (42%) or successfully screened (45%) the majority of their eligible patients. Barriers to HCV screening were diverse across specialty groups with the majority of EM residents concerned about inadequate resources (90%) and issues surrounding minors (90%). IM residents were concerned about higher priority issues (85%) and time constraints (58%). Peds residents were concerned that HCV testing was outside their scope of practice (69%) and that the prevalence was too low (63%). When informed that one-third of individuals diagnosed with HCV were outside of the birth cohort both Peds and EM providers were more likely to consider screening their patients for HCV. Conclusion: IM residents acknowledged the importance of HCV screening and felt it was appropriate to screen in all settings but identified challenges to screening. Barriers to HCV screening differed between IM, Peds, and EM residents highlighting opportunities for individualized targeted interventions. Disclosures: All authors: No reported disclosures.